2018
DOI: 10.1101/393223
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of the substrate-engaged 26S proteasome reveal the mechanisms for ATP hydrolysis-driven translocation

Abstract: The 26S proteasome is the primary eukaryotic degradation machine and thus critically involved in numerous cellular processes. The hetero-hexameric ATPase motor of the proteasome unfolds and translocates targeted protein substrates into the open gate of a proteolytic core, while a proteasomal deubiquitinase concomitantly removes substrate-attached ubiquitin chains. However, the mechanisms by which ATP hydrolysis drives the conformational changes responsible for these processes have remained elusive. Here we pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(104 citation statements)
references
References 61 publications
11
93
0
Order By: Relevance
“…. While recent structures reveal a conserved spiral staircase 365 arrangement of Rpt40,61 and PAN 62 , data supporting a rotation of the AAA+ hexamer around 20S, to our knowledge, has not been determined. Nonetheless, similar to our findings with ClpAP, the flexibility and distinct engagement states of the connecting HbYX motifs indicate conformational plasticity across the hexamer:heptamer interface is likely critical for coupling ATP hydrolysis and substrate unfolding with proteolysis.…”
mentioning
confidence: 60%
“…. While recent structures reveal a conserved spiral staircase 365 arrangement of Rpt40,61 and PAN 62 , data supporting a rotation of the AAA+ hexamer around 20S, to our knowledge, has not been determined. Nonetheless, similar to our findings with ClpAP, the flexibility and distinct engagement states of the connecting HbYX motifs indicate conformational plasticity across the hexamer:heptamer interface is likely critical for coupling ATP hydrolysis and substrate unfolding with proteolysis.…”
mentioning
confidence: 60%
“…The ClpX structures reported here resemble those of Yme1 and Rpt 1-6 in the spiral architecture of the hexamer, the positions of subunits that contain a nucleoside triphosphate, the interaction of successive pore-1 loops with two-residue segments of the substrate, and the patterns of substrate engaged and disengaged pore-1 and pore-2 loops in the ring (Puchades et al, 2017;de la Peña et al, 2018;Dong et al, 2019). Thus, ClpXP might also be expected to operate by an SC/2R mechanism, but multiple experimental observations suggest otherwise.…”
Section: Discrepancies Between Clpx Function and Sc/2r-model Predictionsmentioning
confidence: 75%
“…AAA+ protease motors belong to either the classic or HCLR clades (Erzberger and Berger, 2006). For HCLR-clade members ClpX and Lon, the spiral hexamer architectures and pore-1loop interactions with substrate in the axial channel are similar to those for the classic-clade YME1/FtsH and the proteasomal Rpt 1-6 /PAN motors (Puchades et al, 2017;de la Peña et al, 2018;Dong et al, 2019;Majumder et al, 2019;Shin et al, 2019). Thus, from a structural perspective, it is reasonable to suggest that motors from different clades may operate by a common fundamental mechanism.…”
Section: Proteolytic Motors From Different Aaa+ Clades Have Similar Smentioning
confidence: 99%
“…Previously, FtsKαβ has been crystallized as a 6-fold 15 symmetrical ring (13), but without dsDNA in the structure, the mechanism by which it translocates has remained unclear. Structures of DNA-or RNA-helicase complexes have suggested that nucleic acids, similarly to peptidic substrate in unfoldases, are generally recognized by a more-or-less asymmetrical ring through motifs organized into a partial helix, akin to a spiral staircase (16)(17)(18)(19)(20)(21).…”
Section: Main Textmentioning
confidence: 99%
“…However, the proposed translocation mechanisms for helicases are based on single-stranded 20 nucleic acids, and it remains to be seen if similar mechanisms apply to motors translocating on more rigid double stranded DNA substrates. 4 Here, we solved by electron cryo-microscopy (cryo-EM) structures of FtsKαβ from Pseudomonas aeruginosa bound to dsDNA.…”
Section: Main Textmentioning
confidence: 99%